Harnessing Bloom’s Digital Taxonomy for Modern Arabic Language Instruction in Islamic Universities - Azkia Muharom Albantani; Agus Sufyan; Abd. Rozak; Muhamad Jaeni; Ade Arip Ardiansyah (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2026)
This study explores the application of Digital Bloom’s Taxonomy in Arabic learning to provide structured and diverse educational experiences that improve student understanding and mastery of the language. Utilizing an exploratory approach, the study engaged Arabic lecturers from nine public institutions across Sumatra and Java through a self-report survey based on Bloom’s Digital Taxonomy. The data analysis revealed a generally positive attitude towards technology integration among lecturers, though areas such as online lecture attendance and addressing student differences require improvement. The findings suggest that while educators possess strong technical, pedagogical, and content knowledge, there is a need to enhance the use of online media platforms and the understanding of Arab culture in teaching. The study highlights the importance of adopting Digital Bloom’s Taxonomy to optimize digital tool usage across various cognitive levels and offers practical guidance for Arabic educators. By addressing these areas, educators can provide a more comprehensive and engaging learning experience, ultimately preparing students for success in a digitally driven world. Further research is necessary to refine pedagogical strategies and evaluate long-term linguistic proficiency and cultural competence outcomes.